The Role of Teacher Competence in Improving the Quality of Learning in Public Elementary Schools - Fitriyah, Fitriyah; Fauzi, Imron (Riviera Publishing, 2025)
The quality of learning in elementary schools depends heavily on four core teacher competencies: pedagogical, professional, social, and personality. This study aims to identify the specific role of each of these competencies in improving the quality of elementary education. It aims to analyze the role of teacher competencies—pedagogical, professional, social, and personality—in improving the quality of the learning process in elementary schools. This study used a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation studies in several public elementary schools. It was found that pedagogical competency enables teachers to design learning that is engaging, innovative, and relevant to student characteristics. Professional competency is reflected in mastery of material and the ability to select effective strategies and media. Meanwhile, social and personality competencies play a crucial role in creating harmonious interactions, building emotional closeness, and fostering a positive and conducive learning environment. The overall quality of learning has been shown to be significantly influenced by the integrated application of these four competencies. The quality of learning in elementary schools is significantly influenced by the full integration of teachers' pedagogical, professional, social, and personality competencies. Therefore, improving teacher professionalism through training, mentoring, and continuous evaluation is an essential step to advance the quality of elementary education.